2021
DOI: 10.1039/d0se01278e
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the oxygen evolution activity in non-stoichiometric praseodymium ferrite-based perovskites by A site substitution for alkaline electrolyser anodes

Abstract: Sustainable fossil fuel free systems are crucial for tackling climate change in the global energy market, and the identification and understanding of catalysts needed to build these systems plays a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…6 a. According to this graph, there must be at least a very thin oxide layer must be present on the samples surface, evidenced by the O1s and OKLL peaks [ 54 ]. The binding energy peak position of the O1s are: As-cast − 529 ​± ​1 ​eV, as-cast after ion etch −529 ​± ​1 ​eV, after incubation in water for 48 ​h − 531 ​± ​1 ​eV, after incubation in artificial saliva for 48 ​h − 532 ​± ​1 ​eV.…”
Section: Resultsmentioning
confidence: 99%
“…6 a. According to this graph, there must be at least a very thin oxide layer must be present on the samples surface, evidenced by the O1s and OKLL peaks [ 54 ]. The binding energy peak position of the O1s are: As-cast − 529 ​± ​1 ​eV, as-cast after ion etch −529 ​± ​1 ​eV, after incubation in water for 48 ​h − 531 ​± ​1 ​eV, after incubation in artificial saliva for 48 ​h − 532 ​± ​1 ​eV.…”
Section: Resultsmentioning
confidence: 99%
“…The surface engineering by etching, cation or anion substituting, and heteroatom doping for transition-metal sulfide can effectively improve their activity, , and the enhanced catalytic activities were attributed to the synergistic defects or vacancy sites on the surfaces. Thus, the introduction of defects and vacancies to the catalyst surface is considered to be one of the most effective surface decoration strategies to generate more active sites and promote the charge transfer ability. , Therefore, the electrocatalytic activity is boosted, because of not only the increased active surface area but also the optimized adsorption capacity of the reaction intermediates. , In addition, the defect can also increase the hydrophilicity of the surface to effectively contact the electrolyte . The vacancy is formed by the loss of one or several atoms in the crystal lattice of a metal compound without phase modification, which will cause the electronic structure change of the nearby metal atoms; the defect and vacancy formed in the catalyst system, which, thereby, will impact the adsorption of intermediates during the OER process, and the performance can be boosted as expected. …”
Section: Metal Sulfide Structure Regulationmentioning
confidence: 99%
“…Seroglazova et al synthesized and produced crystalline PrFeO 3 between 612 and 647 °C with a specific surface area of 11.9 m 2 g À1 and a bandgap of 2.07-2.13 eV that could fully degrade methyl violet dye in aqueous solution. [21,22] Tijare et al reported a nanocrystalline PrFeO 3 that evolved hydrogen at 2847 μmol g À1 h À1 in an ethanol-water system under visible light. [23] Freeman et al reported a spray pyrolysis technique to develop pioneering PrFeO 3 photocathodes, calcined at 600 °C, yielding photocathodic response.…”
Section: Introductionmentioning
confidence: 99%